Pengaruh Home Visit terhadap Kepuasan Konsumen Apotek Palasari Sumedang - Zuniarto, Ahmad Azrul; Subagja, Subagja; Nurhasanah, Sarah; Sundari, Retno T; Pandanwangi, Siti (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: In the context of service of pharmaceutical at pharmacy, patients satisfaction is a pleasure feeling appearing in someone’s body after getting service taken directly. The analysis of customer’s satisfaction is based on five dimensions of service quality, which are among others responsiveness, reliability, assurance, empathy, and tangible. The purpose of the research was to find out the influence of home visit activity toward the customer’s satisfaction at Palasari pharmacy Sumedang and the satisfaction level of customer’s satisfaction before and after the home visit activity. This research was a quantitative one where the independent variable was home visit whereas the dependent variable was the customer’s satisfaction at Palasari pharmacy Sumedang. The technic of sample taking was total sampling. The samples used in the research were 34 respondents, they were the PRB patients from Palasari pharmacy at Ganeas district who never take the medicine regularly. The research instruments used in the research was questionnaire of customer’s satisfaction. The results of the study with a questionnaire on the level of consumer satisfaction at Palasari Sumedang Pharmacy before the home visit and after the home visit experienced an increase in percentage results from 75.4% to 81.5% and a simple linear regression test showed that there was an effect of home visits on satisfaction consumer Pharmacy Palasari Sumedang with a value sig. 0.000. Results study show that Home visits are influential to satisfaction consumer Pharmacy Palasari Sumedang with level satisfaction consumers 75.4 % increase to 81.5%.